Study of respiratory and cardiovascular reflex mechanisms involving the lungs - Paintal, A. S. (The University of Edinburgh, 1952)
In the present study of Respiratory and cardio- vascular reflexes of the lungs attention has been particularly directed to the afferent mechanisms involved. This was considered necessary since there is little definite information about the nature of these fibres although much is now known about the jpossible reflexes in which they may participate. with this object a first attack on the problem was made as described in the first part of this thesis by the determination of the conduction velocities of the known vagal thoracic afferents. It is hoped that information so gained will be of value in the interpretation of results of previous investigators. The second part of the thesis presents the results of investigation into the afferent fibre composition of the vagal rootlets as studied by the electrical recording of nerve impulses. This was undertaken because it was hoped that a functional differentiation of the vagal afferents might occur at this level as suggested by the work Beer & Kreidl (1895) and Cadman (I9OO), and thereby provide a means of selective stimulation. This was found not to be the case and further investigation in that field was therefore discontinued. From the work of Dawes, Matt, and Widdicombe (I951) it appeared that certain araidines such as phenyl diguanide are capable of producing a reflex respiratory inhibition which is blocked by cooling the vagi to 31°C. Because of the low blocking temperature it seems possible that this drug affords the means of selective stimulation of small afferents of trie vagus and as will be shown in the 3rd section, this is certainly true. Further in order to test the hypothesis of Dawes et al that the pulmonary vascular afferents described by Whitteridge (1948) were probably concerned in the above reflex, the action of phenyl diguanide on these and other afferents has been studied. Evidence will be presented to indicate that none of the known vagal afferents including the pulmonary vascular ones are sensitized or stimulated by phenyl diguanide.